Implementación de un sistema de control interno al supermercado cercano. ubicado en la provincia de Cotopaxi, cantón Latacunga, sector Lasso, periodo octubre 2015 a febrero 2016 - Pilatasig Chaluisa, Laidy Patricia (2016)
The research work was carried out at the "Cercano" supermarket, it is a company dedicated to marketing of basic necessities products, it has faced some problems concerning the lack of controls, poor communication and failure laws and regulations. The goal is to implement an internal control system that optimizes the use of resources. For this investigation was used the descriptive methodology, in addition, to obtain real and objective information we use the inductive method and deductive synthetic analytic and techniques as interviews and surveys which were addressed to all personnel working in the institution. It was used considering that they are a key factor that directly affects the development of it….